Analysis of COCH and TNFA Variants in East Indian Primary Open-Angle Glaucoma Patients. (26th August 2013) - Chakraborty, Subhadip; Mookherjee, Suddhasil; Sen, Abhijit; Ray, Kunal
Abstract : Glaucoma represents a heterogeneous group of optic neuropathies with a complex genetic basis. It is the second-largest cause of blindness in the world that reduces vision without warning and often without symptoms. Among 3 major subtypes of glaucoma, primary open-angle glaucoma (POAG) is the most common form. The focus of this study is to understand the molecular basis of the disease among Indian patients with respect to two genes, Cochlin ( COCH ) and tumor necrosis factor alpha ( TNFA ), selected based on reports of possible association with POAG. The genes were screened in patients and controls by PCR and direct sequencing. Although two novel changes (–450 C/T and –79 G/G) were identified in the 5′upstream region of COCH, no causal variant could be identified in either gene. –450 C/T was detected in 3 patients and 2 controls and –79 G/C in a single patient. Further, we did not observe significant association with the promoter SNPs of TNFA that had been previously reported to be associated with POAG pathogenesis. Thus, our study suggests lack of association of both COCH and TNFA with POAG pathogenesis.